A high-gas-retention, high-thermal-conductivity tire transition layer rubber composition, a mixing method thereof, and a truck tire
Patent Information
- Application Number
- CN202411159778.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-08-22
AI Technical Summary
[0019]本发明由于采用了上述的技术方案,使用片层硅酸盐无机填料替代大部分炭黑,特别是RC-15是一种纳米级的天然矿物填料,其结构主要为片层硅酸盐,能够在橡胶自由体积中形成空间阻隔作用。填料越多,相应的橡胶相越少,自由体积越小,配方的保气性能就越好。利用无机填料的堆积效应,改善现有全钢载重子午线轮胎过渡层配方功能单一的问题,增加配方对气体的阻隔作用,改善配方透气系数性能;而且RC-15含有40%左右的三氧化二铝组分,具有良好的导热性能,大量使用后能够明显提升配方导热率及轮胎硫化效率。本发明通过高片层无机填料替代配方中大部分N326炭黑,配方透气系数提升20%左右,降低配方生热的同时可以提高配方20%以上的导热系数。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of new materials technology for tire manufacturing, and in particular to a tire transition layer rubber composition with high air retention and high thermal conductivity, its mixing method, and an all-steel truck tire. Background Technology
[0002] With the development of the heavy-duty truck market, research on all-steel radial truck tires has become increasingly sophisticated, and the roles of each tire component have become clearer. Currently, the inner liner of all-steel radial truck tires is mainly composed of a transition layer and an airtight layer. The transition layer, to ensure tire stability, prioritizes carcass performance, resulting in poorer air retention. The airtight layer primarily provides support for tire air retention. Early tests showed that a 10% improvement in the inner liner's air retention significantly reduced the shoulder return rate of all-steel radial tires (a 20%-30% reduction in the cyclic return rate of a certain 12R specification after 36 months). Thermal conductivity is a crucial indicator of tire performance, directly affecting temperature distribution and heat transfer during driving. Thermally conductive fillers in the tire compound can rapidly conduct heat from the tire surface to the tire carcass, thereby reducing localized overheating, improving the tire's thermal balance, and enabling the tire to maintain good performance in high-temperature environments. As carbon black is currently the main thermally conductive filler in all-steel tire formulations, with the introduction of carbon reduction requirements and the market's increasing demands for the performance and production efficiency of all-steel tires, it is particularly important to improve existing formulations and enhance their thermal conductivity and air retention performance.
[0003] Currently, the main filler material in all-steel transition layers is carbon black. The spherical structure of carbon determines that its gas retention performance is significantly worse than that of inorganic fillers with a lamellar structure. Furthermore, the thermal conductivity of carbon differs from that of metal elements in inorganic fillers. With the increasing demands for carbon reduction, finding a high-gas-retention and high-thermal-conductivity material to replace traditional carbon black has become an urgent task.
[0004] The applicant filed a Chinese invention patent application (Publication No.: CN109134981A, Publication Date: 2019-01-04) disclosing a rubber composition for the tread of a high-performance tire. This rubber composition comprises 100 parts by weight of at least one rubber component selected from natural rubber, polyisoprene rubber, polybutadiene rubber, and styrene-butadiene copolymer rubber, and 0.5 to 40 parts by weight of (a) a nano-scale surface-conductive modified silicate, and (b) carbon black and silica, wherein the total amount of components (a) and (b) is 40 to 120 parts by weight. This patent innovatively introduces a nano-scale surface-conductive modified silicate, which, like silica, reduces tire rolling resistance and improves wet grip while also increasing tire conductivity. This allows for an increase in the amount of silica used within the legally permissible resistance range, thereby further reducing rolling resistance and improving wet grip.
[0005] The applicant filed a Chinese invention patent application (Publication No.: CN115322463A, Publication Date: 2022-11-11) disclosing a low-heat-generating, fatigue-resistant rubber composition for producing air springs, its preparation method, and its application. The rubber composition is prepared by mixing raw materials comprising the following components in 100 parts by weight of rubber components: 100 parts chloroprene rubber, 20-40 parts carbon black, 5.0-30 parts silicate silica, 1.0-5.0 parts silane coupling agent, 5.0-20 parts nano-sheet silicate, and 0-0.8 parts organic sulfur donor. The air spring produced by this patent has lower heat generation and superior fatigue resistance.
[0006] The addition of nano-sheet silicates to the aforementioned rubber is generally for the purpose of reducing heat generation. Laminated materials are also added to all-steel radial tires, typically used in the airtight layer. The rubber material used in the airtight layer is halogenated butyl rubber. For example, Chinese invention patent application (publication number: CN115975303A, publication date: 2023-04-18) discloses an airtight layer compound for all-steel radial tires, which is prepared by mixing the following components in parts by weight: 80 parts halogenated butyl rubber, 40 parts laminated material, 40 parts carbon black, 2 parts magnesium oxide, 2 parts zinc oxide, 4 parts stearic acid, 2 parts homogenizer, 3 parts processing oil, 0.5 parts sulfur, and 1.5 parts accelerator.
[0007] Furthermore, reclaimed rubber is one of the main products of the comprehensive utilization of waste tires and waste rubber. The application of reclaimed rubber not only reduces the cost of rubber products and improves economic efficiency, but also plays a significant role in conserving rubber resources and protecting the environment, embodying the circular economy in the rubber industry. As per the applicant's Chinese invention patent applications (CN101628994A, CN101624454A, CN101628993A, CN101628995A, and CN101628992A, etc.), reclaimed rubber is generally used in the tire carcass, tread, sidewall, and outer protective layer. However, its application in the tire transition layer can affect its performance. Therefore, it is necessary to design a suitable formulation that allows reclaimed rubber to be used in the transition layer without affecting its performance. Summary of the Invention
[0008] To address the aforementioned problems, the purpose of this invention is to provide a tire transition layer rubber composition with high air retention and high thermal conductivity. This composition primarily uses lamellar silicate inorganic fillers to replace most of the carbon black, applied to the transition layer formulation of all-steel radial tires. This reduces the air permeability coefficient of the transition layer formulation, improving the tire's air retention performance; it also enhances the thermal conductivity of the transition layer formulation, improving the heat transfer efficiency within the tire.
[0009] To achieve the above objectives, the present invention adopts the following technical solution: A tire transition layer rubber composition with high air retention and high thermal conductivity, characterized in that the rubber composition is prepared by mixing raw materials of the following components in mass fraction: Natural rubber: 100 parts Reclaimed rubber: 5-30 parts Lamellar silicate filler: 70-110 parts Carbon black: 0-15 parts Tackifying resin: 1-8 parts Meta-methyl resin: 0.3-1.2 parts Nickel salt: 0.3-1.2 parts; The layered silicate filler has a D50 particle size of less than 1 micrometer and its main components are 30-45% aluminum oxide and 35-50% silicon dioxide.
[0010] Preferably, the rubber composition is prepared by mixing raw materials containing the following components in a mass fraction: Natural rubber: 100 parts Reclaimed rubber: 10-20 parts Laminated inorganic filler: 90-100 parts Carbon black: 5-10 parts Tackifying resin: 3-6 parts Meta-methyl resin: 0.5-1.0 parts Nickel salt: 0.5-1.0 parts.
[0011] Preferably, the lamellar inorganic filler is RC-15 lamellar silicate inorganic filler provided by China Beyer Trading (Hong Kong) Co., Ltd., whose main components are 38% aluminum oxide and 42% silicon dioxide.
[0012] Preferably, the active agent is 1-8 parts, preferably 3-6 parts; the binder is 2-6 parts, preferably 3-5 parts; the antioxidant is 0-3 parts, preferably 0.5-2 parts; the accelerator is 0.5-2 parts, preferably 1-1.5 parts; and the sulfur is 1-8 parts, preferably 3-6 parts.
[0013] As a preferred option, the antioxidant is selected from 0.3-0.8 parts of antioxidant 4020 and 0.8-1.5 parts of antioxidant RD; the sulfur is selected from 3.0-4.5 parts of insoluble sulfur and 0.8-1.5 parts of 10% oil-extended sulfur.
[0014] As a preferred choice, the reclaimed rubber used is GZ-12 reclaimed rubber and GZ-16 reclaimed rubber from Shanxi Beihai Rubber Co., Ltd., with GZ-12 reclaimed rubber being the preferred option.
[0015] Preferably, the carbon black is selected from one or more of N326, N330, N375, N550, N660 and N774, with N326 or N375 being the preferred carbon black.
[0016] As a preferred option, boron-acylated nickel salt is selected; Preferably, the tackifying resin is one or more of p-tert-butyl tackifying resin, p-tert-octyl tackifying resin, acetylene tackifying resin and ethylene tackifying resin, with p-tert-octyl tackifying resin being preferred. Preferably, the activator is one or more of zinc oxide and stearic acid.
[0017] Furthermore, the present invention also discloses a mixing method for a tire transition layer rubber composition with high air retention and high thermal conductivity, the method comprising the following steps: 1) First stage mixing: Rubber, carbon black, and inorganic filler RC-15 are put into an internal mixer and mixed for 30-50 seconds at a speed of 45-60 rpm. The mixture is lifted and pressed every 20-35 seconds. When the temperature of the rubber compound reaches 155℃-170℃, the rubber is discharged and sheeted. After cooling at room temperature for 8-12 hours, the first stage masterbatch is obtained, which is then subjected to second stage mixing. 2) Two-stage mixing: The first-stage masterbatch from step 1), inorganic filler RC-15, antioxidant, and other rubber processing aids are put into an internal mixer and mixed at a speed of 40-55 rpm. The mixture is lifted and compressed every 20-35 seconds. When the temperature of the rubber compound reaches 145-160℃, the rubber is discharged and sheeted. After cooling at room temperature for 8-12 hours, the second-stage masterbatch is obtained, which is then subjected to final mixing. 3) Final mixing: The second-stage masterbatch, vulcanizing agent, and accelerator from step 2) are put into an internal mixer and mixed at a speed of 20-30 rpm. The mixture is then lifted and pressed at intervals of 20-30 seconds, 15-25 seconds, and 10-20 seconds. When the temperature of the rubber compound reaches 100-120℃, the rubber is discharged and sheeted. After cooling, the transition layer rubber composition is obtained.
[0018] Furthermore, the present invention also discloses an all-steel heavy-duty truck tire, wherein the transition layer of the tire is obtained by vulcanization of the aforementioned high air retention and high thermal conductivity tire transition layer rubber composition.
[0019] This invention, employing the aforementioned technical solution, replaces most of the carbon black with lamellar silicate inorganic fillers. In particular, RC-15 is a nanoscale natural mineral filler whose structure is primarily lamellar silicate, capable of creating spatial barriers within the free volume of the rubber. The more filler, the less rubber phase, the smaller the free volume, and the better the gas retention performance of the formulation. Utilizing the stacking effect of inorganic fillers, it addresses the issue of the limited functionality of existing all-steel radial truck tire transition layer formulations, increasing the formulation's gas barrier effect and improving its permeability. Furthermore, RC-15 contains approximately 40% alumina, possessing excellent thermal conductivity; large-scale use significantly improves the formulation's thermal conductivity and tire vulcanization efficiency. This invention, by replacing most of the N326 carbon black in the formulation with highly lamellar inorganic fillers, increases the formulation's permeability by approximately 20%, reducing heat generation while simultaneously improving the formulation's thermal conductivity by over 20%. Detailed Implementation
[0020] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the protection scope of the present invention.
[0021] Raw material source: Natural rubber (NR) Malaysia GZ-12 Reclaimed Rubber Ordinary reclaimed rubber, Shanxi Beihai Rubber Co., Ltd. RC-15 Inorganic packing materials, China Beyerdynamic Trading (Hong Kong) Co., Ltd. N326 Carbon Black Commercially available Modified zinc oxide Surfactant, Jiaozuo Xingguang Additives Company SL1801 resin Huachi (Zhangjiagang) Co., Ltd. (Regarding terocinyl tackifying resins) 4020 Anti-aging agents, Shandong Sheng'ao Chemical Technology Co., Ltd. RD Anti-aging agents, Shandong Shangshun Chemical Co., Ltd. SL3022B m-M resin, Huachi (Zhangjiagang) Co., Ltd. Nickel borate Nickel salts, Yangzhou Balong Co., Ltd. OT20 Insoluble sulfur, Shandong Shangshun Chemical Co., Ltd. NS Accelerator, Comay Chemical FA608 Adhesive, commercially available Example 1 The formulation consists of the following materials in parts by weight: 100 parts natural rubber, 16 parts GZ-12 reclaimed rubber, 5 parts N326 carbon black, 90 parts RC-15, 6 parts modified zinc oxide, 4 parts tackifying resin (SL1801), 0.5 parts antioxidant (4020), 1 part antioxidant (RD), 0.8 parts meta-methyl resin (SL3022B), 0.6 parts borate nickel, 3.7 parts OT20 (insoluble sulfur), 1.1 parts 10% oil-extended sulfur, 1.2 parts accelerator (NS), and 4 parts adhesive (FA608).
[0022] The mixing method includes the following steps: 1) First stage mixing: Rubber, carbon black, and inorganic filler RC-15 are put into an internal mixer and mixed for 30 to 50 seconds at a speed of 45 to 60 rpm. The mixture is lifted and pressed every 20 to 35 seconds. When the temperature of the rubber compound reaches 155℃ to 170℃, the rubber is discharged and sheeted. After cooling at room temperature for 8 to 12 hours, the first stage masterbatch is obtained, and then it is mixed in the second stage. 2) Two-stage mixing: The first-stage masterbatch from step 1), inorganic filler RC-15, antioxidant, and other rubber processing aids are put into an internal mixer and mixed at a speed of 40-55 rpm. The mixture is lifted and compressed every 20-35 seconds. When the temperature of the rubber compound reaches 145-160℃, the rubber is discharged and sheeted. After cooling at room temperature for 8-12 hours, the second-stage masterbatch is obtained, which is then subjected to final mixing. 3) Final mixing: The second-stage masterbatch, vulcanizing agent, and accelerator from step 2) are put into an internal mixer and mixed at a speed of 20-30 rpm. The mixture is then lifted and pressed at intervals of 20-30 seconds, 15-25 seconds, and 10-20 seconds. When the temperature of the rubber compound reaches 100-120℃, the rubber is discharged and sheeted. After cooling, the transition layer rubber composition is obtained.
[0023] Example 2 The formulation consists of the following materials in parts by weight: 100 parts natural rubber, 16 parts GZ-12 reclaimed rubber, 5 parts N326 carbon black, 100 parts RC-15, 6 parts modified zinc oxide, 4 parts tackifying resin (SL1801), 0.5 parts antioxidant (4020), 1 part antioxidant (RD), 0.8 parts meta-methyl resin (SL3022B), 0.6 parts borylate nickel, 3.7 parts OT20 (insoluble sulfur), 1.1 parts 10% oil-extended sulfur, 1.2 parts accelerator (NS), and 4 parts adhesive (FA608).
[0024] The mixing method is the same as in Example 1.
[0025] Example 3 The formula consists of the following materials in parts by weight: 100 parts natural rubber, 16 parts GZ-12 reclaimed rubber, 5 parts N326 carbon black, 110 parts RC-15, 6 parts modified zinc oxide, 4 parts tackifying resin (SL1801), 0.5 parts antioxidant (4020), 1 part antioxidant (RD), 0.8 parts meta-methyl resin (SL3022B), 0.6 parts borate nickel, 3.7 parts OT20 (insoluble sulfur), 1.1 parts 10% oil-extended sulfur, 1.2 parts accelerator (NS), and 4 parts adhesive (FA608).
[0026] The mixing method is the same as in Example 1.
[0027] Example 4 The formulation consists of the following materials in parts by weight: 100 parts natural rubber, 16 parts GZ-12 reclaimed rubber, 10 parts N326 carbon black, 72.5 parts RC-15, 6 parts modified zinc oxide, 4 parts tackifying resin (SL1801), 0.5 parts antioxidant (4020), 1 part antioxidant (RD), 0.8 parts meta-methyl resin (SL3022B), 0.6 parts borate nickel, 3.7 parts OT20 (insoluble sulfur), 1.1 parts 10% oil-extended sulfur, 1.2 parts accelerator (NS), and 4 parts adhesive (FA608).
[0028] The mixing method is the same as in Example 1.
[0029] Example 5 The formulation consists of the following materials in parts by weight: 100 parts natural rubber, 16 parts GZ-12 reclaimed rubber, 10 parts N326 carbon black, 82.5 parts RC-15, 6 parts modified zinc oxide, 4 parts tackifying resin (SL1801), 0.5 parts antioxidant (4020), 1 part antioxidant (RD), 0.8 parts meta-methyl resin (SL3022B), 0.6 parts borylate nickel, 3.7 parts OT20 (insoluble sulfur), 1.1 parts 10% oil-extended sulfur, 1.2 parts accelerator (NS), and 4 parts adhesive (FA608).
[0030] The mixing method is the same as in Example 1.
[0031] Example 6 The formulation consists of the following materials in parts by weight: 100 parts natural rubber, 16 parts GZ-12 reclaimed rubber, 10 parts N326 carbon black, 92.5 parts RC-15, 6 parts modified zinc oxide, 4 parts tackifying resin (SL1801), 0.5 parts antioxidant (4020), 1 part antioxidant (RD), 0.8 parts meta-methyl resin (SL3022B), 0.6 parts borate nickel, 3.7 parts OT20 (insoluble sulfur), 1.1 parts 10% oil-extended sulfur, 1.2 parts accelerator (NS), and 4 parts adhesive (FA608).
[0032] The mixing method is the same as in Example 1.
[0033] Example 7 The formula consists of the following materials in parts by weight: 100 parts natural rubber, 16 parts GZ-12 reclaimed rubber, 120 parts RC-15, 6 parts modified zinc oxide, 4 parts tackifying resin (SL1801), 0.5 parts antioxidant (4020), 1 part antioxidant (RD), 0.8 parts meta-methyl resin (SL3022B), 0.6 parts nickel borate, 3.7 parts OT20 (insoluble sulfur), 1.1 parts 10% oil-extended sulfur, 1.2 parts accelerator (NS), and 4 parts adhesive (FA608).
[0034] The mixing method is the same as in Example 1.
[0035] Comparative Example 1 The formulation consists of the following materials in parts by weight: 100 parts natural rubber, 16 parts GZ-12 reclaimed rubber, 59.5 parts N326 carbon black, 6 parts modified zinc oxide, 4 parts tackifying resin (SL1801), 0.5 parts antioxidant (4020), 1 part antioxidant (RD), 0.8 parts meta-methyl resin (SL3022B), 0.6 parts borate nickel, 3.7 parts OT20 (insoluble sulfur), 1.1 parts 10% oil-extended sulfur, 1.2 parts accelerator (NS), and 4 parts adhesive (FA608).
[0036] The mixing method is the same as in Example 1.
[0037] Comparative Example 2 The formulation consists of the following materials in parts by weight: 100 parts natural rubber, 16 parts GZ-12 reclaimed rubber, 44.5 parts N326 carbon black, 15 parts RC-15, 6 parts modified zinc oxide, 4 parts tackifying resin (SL1801), 0.5 parts antioxidant (4020), 1 part antioxidant (RD), 0.8 parts meta-methyl resin (SL3022B), 0.6 parts borate nickel, 3.7 parts OT20 (insoluble sulfur), 1.1 parts 10% oil-extended sulfur, 1.2 parts accelerator (NS), and 4 parts adhesive (FA608).
[0038] The mixing method is the same as in Example 1.
[0039] Comparative Example 3 The formula consists of the following materials in parts by weight: 100 parts natural rubber, 16 parts GZ-12 reclaimed rubber, 20 parts N326 carbon black, 60 parts RC-15, 6 parts modified zinc oxide, 4 parts tackifying resin (SL1801), 0.5 parts antioxidant (4020), 1 part antioxidant (RD), 0.8 parts meta-methyl resin (SL3022B), 0.6 parts borylate nickel, 3.7 parts OT20 (insoluble sulfur), 1.1 parts 10% oil-extended sulfur, 1.2 parts accelerator (NS), and 4 parts adhesive (FA608).
[0040] The mixing method is the same as in Example 1.
[0041] According to national standards, physical performance tests were conducted on Examples 1-6 and the comparative examples, and the specific physical performance is shown in Table 1 below.
[0042] Shore A hardness was determined according to GB / T 531.1-2008; tensile strength, elongation at break, and tensile permanent deformation at 100%, 200%, and 300% elongation were determined according to GB / T 528-2009; air tightness was determined according to GB / T 1038-2000; thermal conductivity was determined according to ISO22007-2; DMA dynamic performance test conditions: frequency 20 Hz, strain 7 ± 2%, temperature scan 60 °C. Table 1 shows the physical property test results of Examples 1-7 and Comparative Examples 1-3. Natural rubber 100 100 100 100 100 100 100 100 100 100 Reclaimed rubber 16 16 16 16 16 16 16 16 16 16 N326 59.5 44.5 20 5 5 5 10 10 10 - RC-15 - 15 60 90 100 110 72.5 82.5 92.5 120 Modified zinc oxide 6 6 6 6 6 6 6 6 6 6 Tackifying resin 4 4 4 4 4 4 4 4 4 4 4020 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 RD 1 1 1 1 1 1 1 1 1 1 meta-methyl resin 0.8 0.8 0.8 0.8 0.8 0.8 0.8 0.8 0.8 0.8 Nickel borate 0.6 0.6 0.6 0.6 0.6 0.6 0.6 0.6 0.6 0.6 0T20 3.7 3.7 3.7 3.7 3.7 3.7 3.7 3.7 3.7 3.7 Oil-filled sulfur 1.1 1.1 1.1 1.1 1.1 1.1 1.1 1.1 1.1 1.1 NS 1.2 1.2 1.2 1.2 1.2 1.2 1.2 1.2 1.2 1.2 adhesives 4 4 4 4 4 4 4 4 4 4 Test data are shown in Table 2 Based on Examples 1-3 and Comparative Examples 1-3, it can be concluded that when inorganic filler RC-15 replaces carbon black in the transition layer, the air permeability and thermal conductivity of the transition layer formulation are significantly improved, and the formulation modulus is also significantly increased. In Example 2, M300 is improved by 21%, the air permeability is improved by more than 15%, the thermal conductivity is improved by 20%, and the loss factor at 60°C is significantly reduced. The performance meets the requirements for the use of transition layer rubber in all-steel radial tires and can be used as a high air retention, high thermal conductivity, and low heat generation transition layer in all-steel radial tires.
[0043] Based on Examples 4-7 and Comparative Examples 1-3, it can be concluded that after replacing 35 parts of N326 carbon black with 82.5 parts of RC-15, the modulus, air permeability and thermal conductivity of the formulation in Example 4 are significantly improved. The performance meets the requirements for use as an airtight layer rubber for all-steel radial tires and can be used as a high-modulus, high-air-retention and high-thermal-conductivity transition layer in the formulation of all-steel radial tire transition layers.
[0044] The foregoing description of embodiments of the present invention, through which those skilled in the art are able to implement or use the present invention, will be readily apparent to those skilled in the art. Various modifications to these embodiments will be readily apparent to those skilled in the art. The general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the present invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novelty disclosed herein.
Claims
1. A tire transition layer rubber composition with high air retention and high thermal conductivity, characterized in that, This rubber composition is prepared by mixing the following components in parts by mass: 100 parts natural rubber; 10-20 parts GZ-12 reclaimed rubber; 90-100 parts RC-15 lamellar silicate inorganic filler; 5-10 parts N326 carbon black; 3-6 parts p-tert-octyl tackifying resin; 0.5-1.0 parts m-methyl resin; 0.5-1.0 parts borylated nickel; 3-6 parts activator; 3-5 parts adhesive; 0.5-2 parts antioxidant; 1-1.5 parts accelerator; 3-6 parts sulfur; The RC-15 lamellar silicate inorganic filler has a D50 particle size of less than 1 micrometer and its composition includes 38% aluminum oxide and 42% silicon dioxide.
2. The tire transition layer rubber composition with high air retention and high thermal conductivity according to claim 1, characterized in that, The antioxidants used are antioxidant 4020 (0.5-0.8 parts) and antioxidant RD (0.8-1.5 parts); the sulfur used is insoluble sulfur (3.0-4.5 parts) and 10% oil-extended sulfur (0.8-1.5 parts).
3. The tire transition layer rubber composition with high air retention and high thermal conductivity according to claim 1, characterized in that, The activator is selected from one or more of zinc oxide and stearic acid.
4. An all-steel heavy-duty truck tire, characterized in that, The transition layer of the tire is obtained by vulcanization of a tire transition layer rubber composition with high air retention and high thermal conductivity as described in any one of claims 1-3.
Citation Information
Patent Citations
Sizing material utilizing tire tread rubber of reclaimed rubber, mixing method and application thereof
CN101624454A
Tire side rubber material utilizing regenerated rubber as well as blending method and application thereof
CN101628992A
Tire belted layer rubber material utilizing regenerated rubber as well as blending method and application thereof
CN101628993A
Tire body rubber material utilizing regenerated rubber as well as blending method and application thereof
CN101628994A
Tire external-protection layer rubber material utilizing regenerated rubber as well as blending method and application thereof
CN101628995A